Room Temperature Phosphorescence Emission From Multi-States - Zhang, Xiaofeng; Zhang, Beibei; Luo, Ji; Guo, Song; Wei, Chun; Gong, Yongyang (Frontiers in Chemistry, 2022)
Organic room temperature phosphorescence (RTP) materials have received considerable attention due to their fascinating photophysical properties. During the past decade, various organic luminogens exhibiting RTP emission in solid states were reported. However, the phosphorescence emission of organic compounds can hardly be observed in their solutions at room temperature. Herein, we reported two fluorene derivatives which can emit RTP in degassed organic solvents, polymer doped film and crystalline states. Furthermore, those RTP luminogens emitted different color with different phosphorescence lifetime in multi-states. These results indicated that the phosphorescence performance can be adjusted flexibly in different condensed states. To our knowledge, this is the first example possessing diverse organic RTP at multi-states including solution state.